Preliminary Prediction of the Increase in Flood Hazard from Wind Surges for the City of Elbląg Due to Climate Change - Michał Szydłowski; Abdata Wakjira Galata; Khansa Gulshad (Applied Sciences)
This study investigates the potential increase in flood hazard in the city of Elbląg, Poland, due to the climate-induced intensification of wind surges in the Vistula Lagoon. Using the HEC-RAS 2D (version 6.6) model—typically applied to riverine systems but here adapted for wind-driven lagoon dynamics—we simulate both historical and hypothetical storm events to evaluate water level changes under varying wind speeds. Model validation was performed using the January 2019 surge event, demonstrating strong agreement with observed water levels (NSE > 0.93). Subsequent simulations using synthetic wind scenarios show that extreme NE winds of 35 m·s−1 could raise water levels above 3.5 m asl, significantly surpassing warning and alarm thresholds. The results reveal a non-linear response between wind speed and water accumulation, underscoring the elevated hazard for low-lying areas such as Żuławy Elbląskie. The novelty of this study lies in the innovative application of HEC-RAS to a wind-driven lagoon environment and in the generation of synthetic surge scenarios for climate resilience planning. These findings provide critical insight for improving flood risk assessment and infrastructure adaptation in the face of ongoing climate change.